Labour's First Year : 1945-46 (London : Common Wealth Publications Committee, 1946)
1946 1946 1940s 27 pages better than any conceivable Tory plan we cannot hail it as a Socialist measure, for it attempts to incorporate too many things which are incompatible with the socialist conception of society. In our view a truly socialised medical profession is one which, while being ultimately responsible to the Minister, would have the maximum amount of decentralisation, and a much greater participation at all levels of administration of the people providing and using the Service. The Service would be a whole-time salaried one. Working at different levels would be councils or committees within a national framework composed of roughly equal numbers of elected representatives of both the professions concerned and of the general public. An observer appointed by the Minister would be present to advise the committee and to report to the Minister. At the lowest level these committees would deal with day-to-day local services, and every professional man or woman working in the Service in that locality would have the right to appear before the committee to put forward proposals or to lodge complaints. By these means the factor of economic competition (preserved at present by the capitation payment) would be eliminated, and the way opened for full collaboration and co-ordination of effort between colleagues working in the same area in one Service. The fear of unnecessary and irritating interference from higher authority can only be allayed when the governed have : (a) ease of access to that authority; (b) control over that authority through the ballot ; (c) an organisation designed to encourage the contribution of the individual to the administration of the Service to which he belongs. These assurances are absent from the proposed N.H.S. and, at both regional and local administrative levels, the hand of central authority is much too evident. Will the Proposed Service Work? Having pointed out its grave weaknesses from the Socialist viewpoint, Common Wealth unhesitatingly pronounces this Bill to be a very good reform of the present health services. As a reform it will be more efficient than to-day's unco-ordinated activities because it embodies a large measure of that co-ordination which is so demonstrably overdue. It will not achieve the results its promoters hope for because it has not issued the challenge which socialism, in action as well as words, must make to the existing conception of man's motivating principles. Eventually that challenge will have to be made. This Bill merely postpones the date. 15 15X/2/98/21